2011
DOI: 10.1002/pssc.201100256
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature photoluminescence intensity enhancement in GaAs1‐xBix alloys

Abstract: The optical properties of GaAs1‐xBix alloys with Bi compositions between 0.022 and 0.06 have been studied by photoluminescence (PL). The samples were grown at 400 °C using molecular beam epitaxy. At room temperature, the incorporation of Bi in GaAs reduces the band gap by 64 meV/%Bi with peak wavelength of 1.2 µm for x = 0.06. It was found that room temperature PL intensity increased with Bi composition, but decreases with composition at 10 K. The results at 10 K suggest that the incorporation of Bi degrades t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
1
2
0
2
Order By: Relevance
“…Even though different techniques were used to measure the band gap, the experimental data obtained from this work is consistent with data in the literature. Our previous study found that the band gap of GaAs 1− x Bi x reduces linearly at a rate of 64 meV/%Bi for x up to 0.06 . However, this work shows that for higher Bi concentrations, the band gap reduction becomes nonlinear, as already reported in the literature by several groups .…”
Section: Resultssupporting
confidence: 78%
“…Even though different techniques were used to measure the band gap, the experimental data obtained from this work is consistent with data in the literature. Our previous study found that the band gap of GaAs 1− x Bi x reduces linearly at a rate of 64 meV/%Bi for x up to 0.06 . However, this work shows that for higher Bi concentrations, the band gap reduction becomes nonlinear, as already reported in the literature by several groups .…”
Section: Resultssupporting
confidence: 78%
“…In contrast, for relatively low excitation intensities -such as in our case-the PL intensity decreases with increasing temperature, shows a plateau area with rather weak temperature dependence in the intermediate temperature range, and then gradually decreases when the temperature is further increased up to RT; cf. Fig 2. The anomalous plateau in the PL thermal quenching in Ga(As,Bi) at intermediate temperatures has been observed recently in several studies [10,12].…”
Section: Experimental Observationsmentioning
confidence: 83%
“…Сплошной черной линией представлена полученная в работе [25] линейная подгоночная зависимость вариации ширины запрещенной зоны материала GaAs 1−x Bi x от концентрации Bi: E = −6.4x. Как видно, данная аппроксимация количественно описывает измеренную нами зависимость.…”
Section: Growthunclassified
“…Оптические исследования подтвердили, что относительно небольшое содержание висмута приводит к весьма существенному сужению запрещенной зоны материала. Принимая во внимание влияние хвостов зон, вызванных формированием антиструктурных дефектов мышьяка, изменение ширины запрещенной зоны, вызванное формированием твердого раствора GaAs 1−x Bi x , можно описать линейным законом E = −6.4x, экспериментально полученным в работе [25]. Достигнутое нами максимальное уменьшение запрещенной зоны, связанное с формированием твердого раствора GaAs 1−x Bi x , составляет ∼ 0.14 эВ при содержании висмута ∼ 2 мол% и реализуется при температуре эпитаксии 200 • C.…”
Section: обсуждение результатовunclassified